Engineering Iron Oxide Hollow Nanospheres to Enhance Antimicrobial Property: Understanding the Cytotoxic Origin in Organic Rich Environment. (21st June 2016) - Nor, Yusilawati Ahmad; Zhou, Liang; Meka, Anand Kumar; Xu, Chun; Niu, Yuting; Zhang, Hongwei; Mitter, Neena; Mahony, Donna; Yu, Chengzhong
Abstract : Engineered magnetic iron oxide nanoparticles with surprisingly high antimicrobial activity and excellent safety profiles to mammalian cell lines have been developed. Hematite hollow nanospheres (HNSs) are prepared by a facile hard templating method; reduction of hematite HNSs by H2 leads to magnetite HNSs. The antimicrobial activity of magnetite HNSs towards Gram negative ( Escherichia coli ) and Gram positive ( Staphylococcus epidermidis ) bacteria is evaluated against hematite HNSs and conventional magnetite (C‐magnetite; diameter <50 nm). Superior antibacterial performance is observed for magnetite HNSs towards both E. coli and S. epidermidis over hematite HNSs and C‐magnetite. The origin of the antimicrobial activity of magnetite HNSs is the high leaching of iron ions in the presence of microorganisms, which leads to high generation of reactive oxygen species. Magnetite HNSs allow multiple‐fold increase in the generation of soluble iron ions over hematite HNSs and C‐magnetite, showing that control over both the composition and nanostructure is crucial to tune the antimicrobial activity of iron oxides. Based on the current findings, magnetic HNSs show promising potential antimicrobial applications. Abstract : A novel strategy for preparing iron oxide nanoparticles with surprisingly high antimicrobial activity and excellent safety to mammalian cells is developed. Magnetic hollow nanospheres (HNSs) have superior antimicrobial activity as compared to hematite HNSs and conventional magnetites, signifying that control over both the composition and nanostructure is crucial to tune the antimicrobial activity and biosafety of iron oxides.